Answer:
Step-by-step explanation:
Negative 2/3 means -2/3
Hence;
1 + (-2/3) - (-m)
= 1 - 2/3 + m (positive x negative = negative, negative x negative = positive)
Substituting 9/2 for the value of m
= 1 - 2/3 + 9/2
The L.C.M = 6
= ( 6 - 4 + 27)/6
= 29/6
Answer:
Step-by-step explanation:
Answer:
my answer for y is -6, x is -10
Step-by-step explanation:
just eliminate the -4s by subtracting them and you will get the value of y.
now you can use either eqn (I) or (ii) which are first and second.
anyone you decide to choose just replace y by the value you got and you will get the value of x.
pls try to do it buddy you can
Answer:
100,000,000,000
Step-by-step explanation:
1 000 000 times 100 000 = 100,000,000,000
Step-by-step explanation:
6x-7
= 6×2-7
=12-7
=5
b) 3x
=3×2
=6